Ultrasound-assisted green synthesis of functionalised xanthene derivatives: Advancing sustainable sonochemical strategies - Sasadhar Majhi; Sivakumar Manickam; Giancarlo Cravotto (Ultrasonics Sonochemistry)
Xanthenes are an important class of heterocycles in medicinal chemistry due to their diverse pharmacological properties. These tricyclic aromatic compounds, characterised by a dibenzo[b,e]pyran core with an oxygen atom at their central position, have gained significant attention for their extensive applications. Beyond pharmaceuticals, xanthenes are widely used in textiles, food industries, electro-optical devices, dyes, and bioimaging agents. Xanthene derivatives, particularly 9‐substituted xanthenes, exhibit a wide range of biological activities, including antiparasitic, antibacterial, antileishmanial, cytotoxic, neuroprotective, and photophysical effects, making them valuable in drug discovery. The xanthene scaffold is present in various bioactive natural compounds such as mulgravanols A and B, hermannol, (+)-myrtucommulone D, homapanicones A and B, blumeaxanthene II, and acrotrione. Clinically relevant xanthene-based drugs include propantheline bromide (antimuscarinic), methantheline (antispasmodic), and phloxine B (photosensitiser in antimicrobial therapy). Thus, various synthetic approaches have been developed for the construction of xanthenes, with ultrasound-assisted green methodologies gaining prominence. Ultrasound technique offers advantages over conventional methods, including higher yields, faster reaction rates, and improved selectivity under milder conditions. This review comprehensively explores the ultrasound-assisted synthesis of functionalised xanthene derivatives as an eco-friendly alternative. To the best of our knowledge, this is the first in-depth review focusing on the green methodology under ultrasound irradiation.